Dual-Specificity Tyrosine Phosphorylation-Regulated Kinase 1B Inhibition Promotes Megakaryocyte Polyploidization and Platelet Production - Zhao, Jiaxin; Xu, Yanyan; Wang, Jiqiu; Liu, Junling; Zhang, Ruiyan; Yan, Xiaoxiang (Thrombosis and Haemostasis, 2022)
Platelets are produced from mature megakaryocytes which undergo polyploidization and proplatelet formation. Cell-cycle regulation plays a crucial role in megakaryocyte terminal differentiation especially in polyploidization. Dual-specificity tyrosine phosphorylation-regulated kinase 1B (DYRK1B) controls cell-cycle progression in cancer cells. The objective of this study was to determine DYRK1B function in megakaryocyte maturation and platelet production. A DYRK1B knock-out mouse was generated with increased peripheral platelet count compared with the wild type mouse without affecting megakaryocyte numbers in bone marrow. Polyploidy and proplatelet formations were significantly enhanced when DYRK1B was depleted in vitro. DYRK1B inhibition promoted megakaryocyte maturation by simultaneously upregulating cyclin D1 and downregulating P27. Furthermore, there was platelet restoration in two mice disease models of transient thrombocytopenia. In summary, DYRK1B plays an important role in megakaryocyte maturation and platelet production by interacting with cyclin D1 and P27. DYRK1B inhibition has potential therapeutic value in transient thrombocytopenia treatment. Graphic Abstract
Keywords: platelet production; DYRK1B; cyclin D1; P27